African American Stepfather–Stepchild Relationships, Marital Quality, and Mental Health. Issue 6 (17th August 2016) - Bryant, Chalandra M.; Futris, Ted G.; Hicks, Megan R.; Lee, Tae-Kyoung; Oshri, Assaf
ABSTRACT: This study examined associations between stepfather–stepchild relationship quality, stepfathers' depressive symptoms, and two aspects of marriage: marital quality and positive marital interactions. Marital quality was assessed in terms of commitment, trust, passionate and friendship-based love, and happiness. Marital interactions were assessed in terms of intimacy, shared activities, and verbal communication. Using data collected from 149 recently married African American stepfathers, structural equation modeling revealed that when stepfathers reported more positive relationships with their stepchildren, they also reported more positive marital quality and a higher frequency of positive marital interactions (relationship-solidifying activities), and that, in turn, was associated with stepfathers experiencing fewer depressive symptoms.